Current Enzooticity of Dirofilaria immitis and Angiostrongylus vasorum in Central and Southern Italy - Donato Traversa; Simone Morelli; Angela Di Cesare; Chiara Astuti; Alessandra Barlaam; Mariasole Colombo; Fabrizia Veronesi; Barbara Paoletti; Raffaella Iorio; Raffaella Maggi; Alessandra Passarelli; Alessia Pede; et al. (Animals)
Dirofilaria immitis and Angiostrongylus vasorum are major parasitic nematodes of dogs. Many environmental and phenological changes have recently modified their geographic patterns in many countries; thus, this study has updated the distribution of D. immitis and A. vasorum in dog populations of selected regions of Central and Southern Italy. Also, collateral data on other endoparasites affecting the study population have been collected. Blood and fecal samples collected from 2000 dogs were tested using Knott’s test and copromicroscopy (i.e., Baermann’s and fecal flotation tests), respectively. Binomial logistic regression was performed to evaluate statistically significant associations between positivity for D. immitis and/or A. vasorum and potential risk factors. Overall, 35 (1.7%) and 62 (3.1%) dogs were positive for microfilariae of D. immitis and first stage larvae (L1) of A. vasorum, respectively, while 3 (0.1%) were co-infected by both nematodes. Microfilariae of Dirofilaria repens were found in 148 (7.4%) dogs, while at the flotation, eggs of Ancylostomatidae, Trichuris vulpis, and ascarids were found in the feces of 323 (16.5%), 249 (12.4%), and 172 (8.6%), dogs, respectively. Overall, 217 (10.8%) and 44 (2.2%) dogs were positive for eggs of Capillaria aerophila and Capillaria boehmi. The presence of cardiorespiratory clinical signs or non-specific signs, history of travel, and an age of >4 years old were significantly associated with positivity for D. immitis, while A. vasorum was significantly recorded in dogs with cardiorespiratory signs, or with a history of mollusk ingestion or permanent outdoor housing. These results confirm that D. immitis is enzootic in the investigated regions of Central and Southern Italy, even where it was rare/undetected until recently. Indeed, although some dogs positive for D. immitis had a history of travel in enzootic areas, the majority of them were never moved, indicating that they acquired the parasite in the region where they live. Additionally, A. vasorum is stably enzootic in the study areas, as also are other extraintestinal nematodes (i.e., D. repens and C. aerophila) that are more frequently detected today than in the past. A high level of vigilance and routine parasitological screening are necessary, considering the high prevalence of intestinal parasites in owned dogs that are also co-infected by respiratory parasites. The implementation of chemoprevention against D. immitis in dogs living in the examined area should be encouraged.